Dual-frequency liquid crystals as tunable materials for beam steering in terahertz photonics - Gridyakina, Oleksandra; Chodorow, Urszula; Nieradka, Adrianna; Siemion, Agnieszka; Parka, Janusz; Lesiak, Piotr; Woliński, Tomasz (Photonics Letters of Poland, 2025)
Dual-frequency liquid crystal (LC) materials for tunable beam steering in the 0.1–3.5 THz range were investigated. Recent LC formulations exhibit a low loss tangent, high polarization coefficients, and significant dielectric and optical anisotropies, including suitably high birefringence for effective THz modulation. We have implemented this material in electrically tunable phase shifters and beam-steering elements, demonstrating their ability to operate with low absorption and controllable birefringence. The obtained characteristics suggest that dual-frequency LCs could be used to create compact, efficient, and highly tunable THz photonic and sensing components. This study outlines the performance parameters relevant to practical THz devices and highlights their potential for reconfigurable photonic architectures.